ANALISA MEDIA PENDINGIN KAPUR PADA PROSES TEMPERING TERHADAP SIFAT FISIS PADA POROS S 45 C - Lagiyono .; Siswiyanti .; Waryono . (Engineering : Jurnal Bidang Teknik, 2011)
This research aim to analyse process tempering with lime coolant to property fisis covering assaying of chemical composition and assaying of microstructure at  Axis  S45C. Process quenching at temperature 870°C with detention of 30 minutes and tempering is done with temperature 300°C with detention of 60 minutes  . Assaying applied in this research is descriptive assaying (Assaying destroys) what applies feedstock for specimen  is Axis Steel S45C.  Composition test result shows basis material ( Raw Material) included in faction of medium carbon steel or middle carbon steel with carbon content 0,47%. After getting treatment of Quenching with cooling applies water and Tempering with cooling applies lime then is tested its(the chemical composition and microstructure  happened transformation at chemical composition content and prensentase its(the microstructure.  As for result of assaying after getting treatment process of tempering happened transformation of chemical composition that is improvement at Mn ( Manganese) out of 06308 % becomes 063131 %, Si ( Silicon) out of 023283 % becomes 023806 %, Al ( Aluminum) out of 000992 % becomes 001276 %, Cu ( Copper) out of 00077 % becomes 000859 % and V ( Vanadium) out of 000012 % becomes 000022 %.  For its(the microstructure with content pearlite equal to 95% and ferrite equal to 5% but having strain between sewer structureses is more breadth.  Application from result of this research that axis steel S45C is getting treatment of Tempering with pedingin lime can be applied as axis because memilki strength and hardness but remain to slack is not brittle.Keyword :  Qunching, Tempering, Axis S45C, Microstructure, Metal Chemical Composition